Increasing Children's Creativity through The Use of Natural Materials at BA Aisyiyah Jekani - R Ramelah; Sri Slamet (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe in depth the efforts to increase children's creativity through the use of natural materials as learning media at BA Aisyiyah Jekani. The background of this research is based on the importance of developing creativity in early childhood as one of the aspects of development that must be stimulated from an early age. Children's creativity is often underdeveloped because learning activities are still dominated by factory-made or printed media, which provide limited opportunities for children to explore freely. Therefore, teachers need to design learning activities that are concrete, engaging, and contextual by utilizing materials that are easily found in the child's surrounding environment.This research used a qualitative method with a descriptive approach. The research subjects consisted of class A teachers and students at BA Aisyiyah Jekani. Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing.The results show that the use of natural materials such as leaves, twigs, stones, seeds, and sand has a positive impact on increasing children's creativity. Children became more active, enthusiastic, and able to produce various creative works using natural materials from their surroundings. In addition, natural materials were effective in fostering children's learning interest, developing fine motor skills, and instilling a sense of responsibility in maintaining the environment. This study concludes that natural materials are effective learning media in improving learning outcomes and student participation at BA Aisyiyah Jekani.